A longitudinal study of sexual activity and influencing factors in breast cancer patients during treatment in the Southwest of China: a trajectory analysis model - Zhang Tian; Zhang Xiaolu; Yang Jing; Wen Min; Liao Jiaqian; Chen Shouli; Wang Yingyin; Deng Xiaoyuan; Liu Xiaoyan; Wang Guorong (BMC, 2024)
Abstract Purpose The aim of this study was to describe the longitudinal developmental trajectories and its influencing factors of sexual activity in patients with breast cancer during treatment. Methods A prospective longitudinal study was conducted, including 225 newly diagnosed breast cancer patients in A tumor specialty three-class hospital in Southwest China. We measured sexual activity at the time of admission and diagnosis (T0) and one month (T1), three months (T2), six months (T3), and nine months (T4) after diagnosis. A trajectory analysis model (GBTM) was used to explore the changes in sexual activity in breast cancer patients. Multivariate binary logistic regression analysis was used to analyse the factors that affected the classification of sexual activity trajectories. Results The ratio of sexual activity abruptly declined from 100% at baseline to 39.1% at T1. The percentage of sexual activity was improved, from 51.4% at T2 to 63.1% at T4. The optimal model was a 2-group trajectory of sexual activity in breast cancer patients,36.6% in the "low activity group" and 63.4% in the "high activity group." The multivariate binary logistic regression analysis revealed statistically significant and positive correlations between sexual activity and age (β = 0.085, OR = 1.089, 95%CI 1.035 ∼ 1.145, P = 0.001),libido(β = 0.774, OR = 2.168, 95%CI 1.337 ∼ 3.515, P = 0.002), vaginal lubrication(β = 1.254, OR = 33.503, 95%CI 2.000 ∼ 6.137, P<0.001). Conclusions Breast cancer patients exhibited varying levels of sexual activity during treatment; higher age was associated with increased sexual activity, which can contribute to the recovery of sexual function. Therefore, it is crucial to provide appropriate guidance on sexual health for younger patients.